Broad Spectral Response FeOOH/BiO2−x Photocatalyst with Efficient Charge Transfer for Enhanced Photo-Fenton Synergistic Catalytic Activity - Pengfei Wu; Yufei Qin; Mengyuan Gao; Rui Zheng; Yixin Zhang; Xinli Li; Zhaolong Liu; Yingkun Zhang; Zhen Cao; Qingling Liu (Molecules, 2024)
In this work, to promote the separation of photogenerated carriers, prevent the catalyst from photo-corrosion, and improve the photo-Fenton synergistic degradation of organic pollutants, the coating structure of FeOOH/BiO2−x rich in oxygen vacancies was successfully synthesized by a facile and environmentally friendly two-step process of hydrothermal and chemical deposition. Through a series of degradation activity tests of synthesized materials under different conditions, it was found that FeOOH/BiO2−x demonstrated outstanding organic pollutant degradation activity under visible and near-infrared light when hydrogen peroxide was added. After 90 min of reaction under photo-Fenton conditions, the degradation rate of Methylene Blue by FeOOH/BiO2−x was 87.4%, significantly higher than the degradation efficiency under photocatalysis (60.3%) and Fenton (49.0%) conditions. The apparent rate constants of FeOOH/BiO2−x under photo-Fenton conditions were 2.33 times and 3.32 times higher than photocatalysis and Fenton catalysis, respectively. The amorphous FeOOH was tightly coated on the layered BiO2−x, which significantly increased the specific surface area and the number of active sites of the composites, and facilitated the improvement of the separation efficiency of the photogenerated carriers and the prevention of photo-corrosion of BiO2−x. The analysis of the mechanism of photo-Fenton synergistic degradation clarified that ·OH, h+, and ·O2− are the main active substances involved in the degradation of pollutants. The optimal degradation conditions were the addition of the FeOOH/BiO2−x composite catalyst loaded with 20% Fe at a concentration of 0.5 g/L, the addition of hydrogen peroxide at a concentration of 8 mM, and an initial pH of 4. This outstanding catalytic system offers a fresh approach to the creation and processing of iron-based photo-Fenton catalysts by quickly and efficiently degrading various organic contaminants.